A new species of Triphora (Orchidaceae: Triphoreae, Triphorinae) from Mexico - Figueroa, Dante S.; Zabalgoitia, Alejandro; Velázquez-Ríos, Perla; Muñiz-Castro, Miguel Á.; Jiménez-Machorro, Rolando; Guerrero-Hernández, Ricardo; Huerta-Galván, Oassis (Phytotaxa, 2023)
Triphora gallegosii, a new species of geophyte orchid known so far from central, western, and northwestern Mexico, is described and illustrated. This species is morphologically similar to T. gentianioides and T. wagneri, with whom it shares the presence of scale-like leaves, three longitudinal verrucose lines on the lip, and floral parts of similar sizes, but differs from both by its lip lines that vanish towards the middle of the central lobe, having 1–4 resupinate flowers, and flowering between August and September. It also differs from T. wagneri by having a constricted central lobe and lateral lobes with acute apex, and from T. gentianoides by having entire margins on the lateral lobes, column with a magenta apex and whitish towards the middle portion with a green base, magenta anther, smaller leaves, and solitary growth. A preliminary analysis of the conservation status and a dichotomous key to the species of the genus in Mexico are provided.